Gli1 + mesenchymal stromal cells form a pathological niche to promote airway progenitor metaplasia in the fibrotic lung - Cassandras, Monica; Wang, Chaoqun; Kathiriya, Jaymin; Tsukui, Tatsuya; Matatia, Peri; Matthay, Michael; Wolters, Paul; Molofsky, Ari; Sheppard, Dean; Chapman, Hal; Peng, Tien (Nature cell biology, 2020)
Aberrant epithelial reprogramming can induce metaplastic differentiation at sites of tissue injury that culminates in transformed barriers composed of scar and metaplastic epithelium. While the plasticity of epithelial stem cells is well characterized, the identity and role of the niche has not been delineated in metaplasia. Here, we show that Gli1 mesenchymal stromal cells (MSCs), previously shown to contribute to myofibroblasts during scarring, promote metaplastic differentiation of airway progenitors into KRT5 basal cells. During fibrotic repair, Gli1 MSCs integrate hedgehog activation signalling to upregulate BMP antagonism in the progenitor niche that promotes metaplasia. Restoring the balance towards BMP activation attenuated metaplastic KRT5 differentiation while promoting adaptive alveolar differentiation into SFTPC epithelium. Finally, fibrotic human lungs demonstrate altered BMP activation in the metaplastic epithelium. These findings show that Gli1 MSCs integrate hedgehog signalling as a rheostat to control BMP activation in the progenitor niche to determine regenerative outcome in fibrosis.